Sesame Street. [videorecording (DVD)] Monster manners (Sesame Street (Television program), 2014)
Help little monsters learn to mind their manners! Can Rosita control her emotions and keep her hands to herself? Will Prairie help Cookie Monster master polite table manners and can Cookie stop himself and not gobble all the cookies when a Cookie Connoisseur visits Sesame Street?